Effect of cutting regimes on seasonal trends in the carbohydrates reserves of alfafa anid Paspalum guenoarum in mixture - Costa, Newton de Lucena; de Saibro, João Carlos (Pesquisa Agropecuaria Brasileira, 1994)
An experiment was established at the Agriculture Experimental Station of the Federal University of Rio Grande do Sul, to determine the effects of growth stage and stubble height (5 and 10 cm) on the seasonal changes of total non-structural carbohydrates (TNC) reserves of alfalfa (Medicago sativa L.) and Paspalum guenoarum Arech. in mixture. In both species, TNC variations showed periods of depletion and accumulation. There was a significative (P < 0.05) seasonal trend of TNC contents. From August to December, a gradual decrease of TNC contents was observed, followed by reposition periods during Autumn and Spring. In all seasons, clipping at 5 cm stubble height, for both species, independently of growth stage, provided lower TNC contents. Cutting forage at flowering stage at 10 cm stubble height, during spring and winter for alfalfa and, during Spring and Summer for P. guenoarum resulted in the highest TNC contents.